LIMA PRINSIP DASAR PENDIDIKAN PONDOK UNTUK MEMBANGUN SIKAP KETAATAN SISWA MTS DI PESANTREN AN-NAWAWI BERJAN PURWOREJO - Madum, Mohamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
An-Nawawi Islamic boarding school which has five basic educations, namely remembering the afterlife, improving ethics or manners, believing in one's own abilities, obedience, and facing trials. These five basic principles of education are used to form cadres who are able to perceive their knowledge. Indeed, the students in the An-Nawawi Islamic boarding school must be able to carry out the five basic principles of education. However, considering that there are still many students as well as MTs students who have not been able to carry out these five principles, especially in terms of compliance. In this case, the focus of the research is whether Islamic boarding schools have implemented these five basic principles. And how to achieve the five principles of Islamic boarding school education in building the obedience attitude of MTs students. The method used in this study is a qualitative descriptive method and uses a normative approach. In collecting data the researchers used interview, observation and document techniques. To test the validity of the data, the examiner uses the techniques of credibility, transferability, dependability, and confirmability. So it will be easier to analyze and get conclusions in accordance with the provisions. So that it can be concluded that the An-Nawawi Islamic boarding school in general has implemented the five basic principles of Islamic boarding school education in accordance with its provisions, while the achievements of the five basic principles of Islamic boarding school education to build student attitudes in Islamic boarding schools can be said to be good.